ANALISIS DATA KECELAKAAN: (Menggunakan statistik Parametrik dan Non Parametrik) - Ikhwanuddin Ikhwanuddin; Judiono Judiono; M. Djaelani (Journal of Innovative and Creativity, 2026)
Traffic accidents along freight transportation routes constitute a serious problem with significant impacts on safety, social conditions, and the economy. The Ngawi–Sidoarjo National Road, as one of the main logistics corridors in East Java, has a relatively high accident rate. This study aims to analyze the characteristics of road users, freight vehicles, and the factors influencing the occurrence and losses of accidents using both parametric and non-parametric statistical approaches. Freight transportation accident data from the period 2012–2017 were analyzed using SPSS software through descriptive analysis, homogeneity tests, normality tests, comparative tests, correlation analysis, and linear regression. The results indicate that driving behavior variables have the most significant influence on accident intensity and severity, followed by pre-driving inspection variables. Variables related to respondent characteristics, vehicle movement, and vehicle load are associated with accidents, but their effects are relatively smaller. These findings are expected to serve as a basis for improving traffic safety in freight transportation.